Preparation of Al-CeO2-Mg grain refiner for AZ31 Mg alloy via a novel direct melt reaction process - Fan, Wenxue; Bai, Yu; Zuo, Guoliang; Sima, Yapeng; Hao, Hai (Materials letters, 2022)
•Al-CeO2-Mg master alloy is prepared by a novel direct melt reaction process.•Direct melt reaction overcomes the float and agglomeration of raw materials.•The master alloy contains contributing MgAl2O4 particles and Ce-rich compounds.•Al-CeO2-Mg master alloy shows a remarkable grain refinement effect on AZ31 alloy.•MgAl2O4 particles and Ce-rich compounds are the keys to grain refinement. An Al-CeO2-Mg master alloy prepared via a novel direct melt reaction (DMR) process was validated as an effective grain refiner for AZ31 Mg alloy. It was considered that MgAl2O4 particles in grain refiner promoted heterogeneous nucleation and the released Ce solute from grain refiner restricted the growth of Mg grains, which benefited to the grain refinement. This work indicated that the prepared Al-CeO2-Mg master alloy was a promising inoculation agent for AZ31 Mg alloy.